Invasive pneumococcal disease in England and Wales: vaccination implications. - Sleeman, K; Knox, K; George, R; Miller, E; Waight, P; Griffiths, D; Efstratiou, A; Broughton, K; Mayon-White, R; Moxon, E; Crook, D (2001)
Knowledge of the epidemiology of invasive pneumococcal disease (IPD) will aid in planning the use of pneumococcal vaccines. A United Kingdom (UK)-based surveillance in England and Wales (1995-1997) of 11,528 individuals with IPD and a local enhanced surveillance in the Oxford (UK) area (1995-1999) have been analyzed. IPD has a high attack rate in children, with 37.1-48.1 cases per 100,000 infants <1 year old per year, and in older persons, with 21.2-36.2 cases per 100,000 persons >65 years old per year, for England, Wales, and Oxford. The 7-valent conjugate vaccine includes serotypes causing < or =79% of IPD in children <5 years old, but only 66% in adults >65 years old. The data also indicate that IPD varies by serotype, age, and country, emphasizing that the epidemiology of IPD is heterogeneous and requires continued surveillance.